The infinite longing for home : desire and the nation in selected writings of Ben Okri and K.S. Maniam - Lim, David C. L. (Cross/cultures ;, 2005)
The Infinite Longing for Home is a groundbreaking study of Ben Okri's and K.S. Maniam's literary problematization of 'home' in relation to subjectivity and the nation within and beyond the context of Nigeria and Malaysia. Drawing on Lacan, Žižek, Laclau and Mouffe, and weaving through history, politics, philosophy and literature, this book critically examines the motives and means by which peoples forced to live together in a country love and hate each other, and overlook the truths about themselves, their actions and beliefs. It looks into why some embrace heterogeneity and open-endedness whi.